2010
DOI: 10.1111/j.1365-2141.2010.08202.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral meningoencephalitis as complication of Rituximab therapy in a patient treated for diffuse large B‐cell lymphoma

Abstract: Leukocyte reduction and ultraviolet B irradiation of platelets to prevent alloimmunisation and refractoriness to platelet transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
0
26
1
2
Order By: Relevance
“…In addition, the patient had been completely healthy prior to admission, whereas enteroviral CNS infection in healthy adult patients usually manifests as meningeal inflammation only. Enteroviral encephalitis has been reported in a limited number of patients, including several treated with rituximab for hematologic malignancies and neonates [3][4][5]. A recent case report described a previously healthy patient, who presented with rapidly progressive dementia syndrome, who was found to have enteroviral encephalitis as confirmed by RT-PCR [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the patient had been completely healthy prior to admission, whereas enteroviral CNS infection in healthy adult patients usually manifests as meningeal inflammation only. Enteroviral encephalitis has been reported in a limited number of patients, including several treated with rituximab for hematologic malignancies and neonates [3][4][5]. A recent case report described a previously healthy patient, who presented with rapidly progressive dementia syndrome, who was found to have enteroviral encephalitis as confirmed by RT-PCR [6].…”
Section: Discussionmentioning
confidence: 98%
“…Although the clinical course of enteroviral meningitis is usually benign and self-limiting, it may induce meningoencephalitis in immunocompromised patients, such as neonates; patients treated with immunosuppressive agents, including transplant recipients; and patients with agammaglobulinemia [3][4][5]. These patients may experience diffuse cerebral dysfunction, including decreased mentality and seizure.…”
Section: Introductionmentioning
confidence: 99%
“…They can also develop HPeV-3 myocarditis and encephalitis, which are usually limited to neonates [119]. Supporting these observations, individuals undergoing immunosuppressive therapy, for instance, cancer treatment with rituximab, that leads to prolonged B-cell deficiency and hypogammaglobulinemia are susceptible to severe and even lethal enterovirus infections [120].…”
Section: Neutralizing Antibodies In Picornavirus Infectionsmentioning
confidence: 62%
“…Additionally, several reports have demonstrated that patients with lymphoma who have undergone treatment with the anti-B lymphocyte agent rituximab are susceptible to severe enteroviral CNS infections (11,12). In our case, the patient was severely lymphopenic throughout his hospitalization and had been treated with rituximab in the previous year, which likely resulted in a severely compromised ability to mount a neutralizing antibody response to echovirus 18.…”
mentioning
confidence: 85%